Prevalence of smoking and factors affecting smoking behaviour during pregnancy: A sample from Tekirdağ/Gebelikte sigara içme prevalansı ve sigara içme davranışını etkileyen etmenler: Tekirdağ örneği - Levent Cem Mutlu; Gamze Varol Saraçoğlu (Turkish Society of Public Health Specialists, 2014)
Abstract Objective: Smoking during pregnancy leads to serious health problems in the mother and the foetus. In our study, we determined the prevalence of smoking during pregnancy and associated factors in Tekirdağ. Methods: This cross-sectional study was carried out in 2009 in, Tekirdağ. The sample size was calculated as 762 pregnant women. A probability sampling technique was used for sampling; the response rate was 98.3%. Results: The rates for daily and occasional smokers, respectively, were found to be 8.0% and 2.8% in our sample. The total rate of smoking prevalence during pregnancy was found to be 10.8%. Among women who did not smoke during pregnancy, 35.8% were exposed to passive smoke in their homes; 17.5% of pregnant women quit smoking, and 61.8% of these women were able to quit without medical support. We also found that the partner's smoking status, household income had a considerable effect on the smoking behaviour of pregnant women. Conclusions: Primary Health Care Units (PHCUs) must provide information on the dangers of smoking to pregnant women and offer encouragement and support to those who wish to quit. Those who successfully quit should also be helped to avoid postpartum smoking relapse, to which end awareness campaigns and programs need to be developed. Key Words: Pregnancy, smoking, prevalence Özet Amaç: Gebelikte sigara kullanımı anne ve bebekte ciddi sağlık sorunlarına yol açar. Çalışmamızın amacı Tekirdağ ilinde gebelikte sigara kullanım prevalansını ve gebelerde sigara kullanımını etkileyen etmenleri belirlemektir. Yöntem: Kesitsel tipte olan çalışma Tekirdağ ilinde 2009 yılında gerçekleştirildi. Çalışmada örneklem büyüklüğü 762 gebe olarak belirlendi. Örneklem grubu seçilirken olasılıklı örnekleme yöntemleri kullanıldı. Anket geri dönüş hızı %98.3'tü. Bulgular:Gebelikleri sırasında her gün en az bir ve günde birden az sigara içme hızı sırasıyla %8.0 ve %2.8'di. Gebelik süresince sigara içme prevalansı %10.8 bulundu. Sigara içmeyen gebelerin %35.8'inin evlerinde pasif sigara dumanına maruz kaldıkları belirlendi. Kadınların %17.5'i gebelik nedeniyle sigarayı bırakmıştı, bunların %61.8'i tıbbi destek almadığını belirtti. Çalışmada ek olarak eşin sigara içme durumunun ve hane halkı toplam gelirinin gebe kadınların sigara içme davranışını etkilediği bulundu. Sonuç: Birinci basamak sağlık kurumları gebe kadınları gebelikte sigara içmenin tehlikeleri konusunda bilgilendirmeli, sigarayı bırakma yönünde cesaretlendirmeli ve desteklemelidir. Sigarayı bırakmış gebelere de farkındalık eğitim ve programları ile doğum sonrası yeniden başlamayı engelleyecek yönde yardımcı olunmalıdır. Anahtar Kelimeler: Gebelik, sigara içme, prevalans    DOI: http://dx.doi.org/10.20518/thsd.81750